1970
DOI: 10.3329/dujbs.v20i1.8835
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical aspects of <i>Chandbill</i> Oxbow lake of Meherpur, Bangladesh

Abstract: Some physico-chemical parameters of Chandbill Baor, a natural oxbow lake of Meherpur district were studied from September 2006 to August 2007. Air temperature of the study area varied from 18.10 to 32.10°C ( x ± SE : 27.73 ± 1.22°C). The Water temperature (17.10 to 32.10°C; x ± SE: 28.24 ± 1.32°C), Secchi disc depth (8.89 to 53.34 cm; x ± SE : 26.19 ± 4.29 cm), water depth (132.08 to 307.34 cm; x ± SE : 183.93 ± 13.88 cm); total alkalinity (51.3 to 85.5 mg/l; x ± SE : 68.4 ± 3.64 mg/l), total hardness (85.5 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This observation has similarity with the findings of Kabir and Naser (2011) (2) . There is no significant difference (p > 0.05) of means of DO between the Baors.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…This observation has similarity with the findings of Kabir and Naser (2011) (2) . There is no significant difference (p > 0.05) of means of DO between the Baors.…”
supporting
confidence: 92%
“…The mean value of pH 8.29 ± 0.04 recorded in the present study showed that the water of the six baors was alkaline in nature. Kabir and Naser (2011) made similar observations from the Chandbill oxbow lake (2) . According to Trivedi and Raj (1992), the optimum pH range for aquatic life varied from 6.8 to 9.0 (8) .…”
mentioning
confidence: 70%
“…Taken together, continuous monitoring of that area is given prime importance to the researcher. Physico-chemical are one of the important water quality monitoring tools as any disturbance of these parameters may impose detrimental e ect to the living organisms (G.W et al, 2015;Kabir and Naser, 2011). It is worthwhile to mention that any physico-chemical disturbance of the water health ultimately e ect the national socio-economic status of the country.…”
Section: Introductionmentioning
confidence: 99%
“…Every water use requires a certain minimum water quality ensuring no harm to the user (Kabir et al, 2020). At present land use changes, urban human habitation, inland navigation activity as well as major development scheme in terms of road, bridge and other construction works are greatly affecting this freshwater resource (Rubel et al, 2019;Kabir and Naser, 2011).…”
Section: Introductionmentioning
confidence: 99%